KEKERASAN VERBAL YANG TERBENTUK DI KALANGAN GAMER - Aditya Surya Dinata; Siti Arieta, Teguh Setiandika Igiasi (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
Game online is an online game that can be played simultaneously by several people. people. Online games themselves are so addictive among game players or commonly called gamers. In playing online games online, these gamers can communicate with each other online, but sometimes because of the ease of communication, unhealthy communication is found which leads to leads to forms of verbal violence between these gamers. Verbal violence has several forms such as demeaning, name-calling, blaming, cursing, and threatening. This research This research uses a qualitative method with a descriptive approach. This research aims to find out the impact that occurs on gamers as a result of receiving verbal violence. of receiving verbal violence. This research uses the theory of symbolic interaction interaction theory from George H. Mead. The results showed that verbal violence verbal violence among gamers occurs from a variety of unpleasant circumstances in the playing environment. unpleasant circumstances in the play environment. This research also found that gamers who experience verbal violence also occur in women. a woman. Environmental factors are one of the strong reasons verbal violence verbal violence occurs among gamers. Forms of verbal violence in forms of verbal violence in this study such as cursing, demeaning, and insulting which resulted in a sense of trauma felt by the gamers so that they chose to leave. in the sense of trauma felt by gamers so that they choose to stay away from their surroundings and isolate themselves from their surroundings. away from the surrounding environment and isolate themselves from the surrounding environment